An ocean without a shore : a novel - Spencer, Scott (Ecco, an imprint of HarperCollinsPublishers, 2020)
"Since their college days, Kip Woods has been infatuated with Thaddeus Kaufman, who, years later, is a married father of two children and desperately trying to revive a failing career. Kip's devotion to Thaddeus has been life-defining and destiny-altering, but it has been one that Thaddeus has either failed to notice or refused to acknowledge. But over the course of this heated and mesmerizing novel, set against a background of privilege and affluence in Manhattan and the Hudson Valley, Kip will be forced to reckon with the prison of his own making and decide how much he is willing to sacrifice for a love that may never be shared."--Publisher's description.